Analysis of free chlorine concentration changes and of water retention time in a selected real water supply network - Hołota, Ewa (Instal, 2020)
Oversized water supply networks, due to their low water flow velocities, are particularly exposed to the deterioration of quality of water intended for consumption. The paper presents the construction and calibration of a hydraulic model of a selected real water supply network and of a water quality model. By using simulations the network working conditions were analyzed and their influence on water quality concerning free chlorine concentration changes was presented.
Keywords: water network; modeling; water quality